Neutralization of Human Extrinsic (Tissue-Type) Plasminogen Activator in Human Plasma: No Evidence for a Specific Inhibitor - Korninger, C; Collen, D (Thrombosis and Haemostasis, 1981)
Human extrinsic plasminogen activator (EPA), highly purified from a melanoma cell culture fluid is inactivated in human plasma with a half-life (t ½) of 90–105 min. Gel filtration on Ultrogel AcA 34 of mixtures of 125I-labeled EPA and human plasma, incubated at 37°C, revealed the progressive formation of two radioactive components, one with an apparent Mr of 150,000 and one eluting at the void volume. The component with an Mr of 150,000 was identified as consisting at least in part of EPA-α2-antiplasmin complex since: 1) it reacted with antibodies against α2-antiplasmin, but not with antibodies against the other known plasma protease inhibitors, and 2) formation of this component was strongly reduced in plasma specifically depleted in α2-antiplasmin or when the active site of EPA was blocked. The component eluting at the void volume was identified as consisting at least in part of EPA-α2-macroglobulin complex since: 1) it only reacted with antibodies against these two proteins and 2) was not formed in plasma depleted in α2-macroglobulin or when the active site of EPA was blocked.In purified systems α2-antiplasmin inhibited one-chain EPA with a rate constant of 60 M-1s-1 and two-chain EPA with a rate constant of 130 M-1s-1, which corresponds to a t ½ in plasma of 180 min or 90 min, respectively. α2-Macroglobulin inhibited one-chain EPA with a rate constant of 15 M-1s-1 and two-chain EPA with a rate constant of 30 M-1s-1, which corresponds to a t ½ plasma of 4 or 2 hrs.All these findings taken together indicate that EPA is slowly neutralized in human plasma primarily by α2-antiplasmin and to a lesser extent by α2-macroglobulin. There appears to be no specific inhibitor in human plasma, which would inactivate EPA either rapidly or to a significant extent.
Keywords: Extrinsic (tissue-type) plasminogen activator; α2-antiplasmin; α2-macroglobulin; Antiactivator